Sleeping beauty - Andersen; Hans Christian (London Mind to Mind, 2010)
The tale follows Princess Aurora, who is cursed by an evil fairy to fall into a deep sleep on her sixteenth birthday after pricking her finger on a spinning wheel. Despite the efforts of good fairies to mitigate the curse, the princess falls into a magical slumber. A brave prince ultimately discovers her in the hidden castle and awakens her with a true love's kiss, breaking the spell. The story celebrates themes of enchantment, destiny, and the power of love.